Using gamified quizzes to enhance students' English reading comprehension skills - Salim, Malik; Sukarno, Sukarno; Chaudhuri, Jasim; Titania, Fani Nabila; Handayani, Riris; Haq, Ziaul; Maujud, Iswan (Diksi, 2025)
This study sought to determine whether the use of quiz applications significantly impacts reading comprehension skills among students at Junior High School 1 Yogyakarta. The research employed a quasi-experimental design, utilizing pre- and post-tests administered to both control and experimental groups. The instrument of this research was a reading test that was given to 25 students in each class of pre-test and post-test. The data analyzed; the researcher used SPSS version 25. The data showed that in descriptive statistics the mean score from pretest control was 44.07 and 47.87 of pre-experiment while the test was getting more improvement in post-test. In post-control was 66.60 while post-test experiment was 80.63. In normality test showed that the significant score was >0.05 which means this test was normally distributed and homogeneity of variance showed the scores are of significance was >0.05 which meant the test was homogeneity. Finally, to analyze the impact of the quizzes in reading comprehension, the researcher used a paired sample test which showed that those pairs, namely pre-control to post control, were 0.00 which meant <0.05. Therefore, it can be concluded that there was a significantly improvement in students' reading comprehension skill in English used quizzes.